Impact of Quartz/Argillaceous Sandstone and Siliceous/Kaolinitic Claystone Contamination of Drilling Fluid and Filter Cake Properties - Badr Bageri; Mohammed Benaafi; Jaber Al Jaberi; Mashaer A. Alfaraj; Bandar Al-Otaibi (Geofluids)
The drilling fluid must be designed through a comprehensive process to select the right additives, and then must passed through different API standard evaluation processes to ensure the quality. However, the contamination of the drilling fluid with the drilled cuttings caused a significant alteration in the drilling fluid and sealing properties of the drilling fluid. Therefore, many studies have been conducted to identify the effect of different cuttings on the drilling fluid properties. The current work emphasized on the impact of four different cuttings (quartz sandstone, Argillaceous sandstone, Siliceous claystone, and Kaolinitic claystone). The utilized cuttings in this work were selected carefully from different sandstone types to have varied clay content ranged from 0 to 70%. The selected cuttings were prepared and then characterized in term of their mineral composition and particle size distribution. In order to accomplish the objective of this work, the base mud contains zero cutting concentration, after that, an additional four drilling fluid samples were prepared by adding the prepared cuttings in two different concentrations include 5 wt.% and 10 wt.%. Several indispensable tests were conducted to investigate the impact of the added cutting on the rheological properties, filtration performance, filter cake properties, and other primary properties such as the drilling fluid density and pH. The results exhibited that the fluctuation of fluid properties was governed by two factors, one was the cutting concertation and the other was the clay content. Filter cake thickness showed high sensitivity at the low cutting concentration while the other properties were mostly in the acceptable range. On the other hand, at higher concentration, the results fall down into two clusters: cuttings with clay content ranging from 0 to 50% (quartz sandstone cuttings, Argillaceous sandstone, and Siliceous claystone) and cuttings with clay content higher than 50% (Kaolinitic claystone) as shown in details in the result section of this work. This works highlight the important of considering the cutting impact on the drilling fluid properties which ultimately impact the whole drilling operations.